Comprehensive Review of Optimal and Smart Design of Nonlinear Building Structures With and Without Passive Dampers Subjected to Earthquake Loading - Takewaki, Izuru; Akehashi, Hiroki (Frontiers in Built Environment, 2021)
The optimal and smart design of nonlinear building structures with and without passive dampers subjected to earthquake loading is of great concern in the structural design of building structures. The research started around 1980 and many investigations have been conducted. A comprehensive review on this subject is made in this article. After the description of essential features of the optimal design problem of nonlinear building structures under earthquake ground motions, analysis types of optimization problems are explained and the significance of the dynamic pushover analysis is discussed from the viewpoint of analysis of limit states under earthquake ground motions of magnitude larger than the code-specified level. Then, the categorization by the response of frames and dampers was made. In this categorization, several subjects are discussed first: (i) Optimal design of bare nonlinear building frames under seismic loading, (ii) Optimal design of nonlinear dampers for elastic building frames under seismic loading, (iii) Optimal design of linear dampers for nonlinear building frames under seismic loading, (iv) Optimal design of nonlinear building frames with specified nonlinear dampers under seismic loading, (v) Optimal design of nonlinear dampers for specified nonlinear building frames under seismic loading, (vi) Simultaneous optimization of elastic-plastic building structures and passive dampers. Finally, the classification of researches in view of solution strategies is conducted for providing another viewpoint.